2021
DOI: 10.1029/2021ja029190
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Io Plasma Torus From Juno Radio Occultations

Abstract: The jovian moon Io disperses about 1 ton/s of material in the planetary magnetosphere, mainly by sublimation of SO2 from the surface and by its intense volcanic activity. The ejected material supplies the plasma cloud surrounding Jupiter known as Io Plasma Torus (IPT). The radio communication between Juno and the Earth DSN station crosses the IPT near the closest approach. Being a dispersive medium, the IPT introduces a path delay in the signal, which can be analyzed to retrieve the density distribution of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 66 publications
(211 reference statements)
2
21
0
Order By: Relevance
“…The electron density reported in the present study is between <2,000 cm −3 and 2,750 cm −3 , in agreement with the results from the radio occultations. More specifically, the radio occultation during PJ 11 showed a remarkably low electron density compared to other orbits, while the torus appeared slightly thicker (Moirano, Gomez Casajus, et al., 2021; Phipps et al., 2021). This suggests that the position of the IFP of PJ 11 in panel b of Figure 4 may be explained by a density depletion rather than a temperature drop.…”
Section: Discussionmentioning
confidence: 94%
“…The electron density reported in the present study is between <2,000 cm −3 and 2,750 cm −3 , in agreement with the results from the radio occultations. More specifically, the radio occultation during PJ 11 showed a remarkably low electron density compared to other orbits, while the torus appeared slightly thicker (Moirano, Gomez Casajus, et al., 2021; Phipps et al., 2021). This suggests that the position of the IFP of PJ 11 in panel b of Figure 4 may be explained by a density depletion rather than a temperature drop.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, beams of electrons propagate along field lines leading to Transhemispheric Electron Beam (TEB) spots (Bonfond et al., 2008). Juno observations have confirmed the Alfvénic wave power associated with the satellite footprints (Gershman et al., 2019; Moirano, Gomaz Casajus et al., 2021; Moirano, Mura et al., 2021; Sulaiman et al., 2020; Szalay et al., 2020). Szalay et al.…”
Section: Introductionmentioning
confidence: 87%
“…(2018) also suggested that the plasma torus radial distribution from 6 to 8 R J takes ∼15 days from the beginning of eruption (Yoneda et al., 2015). As a result, the connection between the volcanic eruptions on Io and the variations in the plasma environment in Jupiter's magnetosphere is highly complex (Moirano, Gomaz Casajus et al., 2021; Moirano, Mura et al., 2021; Roth et al., 2020). In addition, Kita et al.…”
Section: Introductionmentioning
confidence: 99%
“…The data were weighted on a pass-by-pass basis using the root mean square of the residuals. Additionally, G29 data were de-weighted to take into account possible Io Plasma Torus (e.g., Bagenal, 1994;Moirano et al, 2021) calibration errors. Finally, the one-way passes were de-weighted by a factor of 2, to take into account the poorer stability of the non-coherent link.…”
Section: Observation Geometry and Datamentioning
confidence: 99%